Designing a Tax Administration Reform Strategy : Experiences and Guidelines - Baer, Katherine (IMF Working Papers; Working Paper ;, 1997)
Building on previous FAD work in the tax administration field, this paper defines broad criteria for diagnosing the problems in a country's tax administration and formulating an appropriate reform strategy. To be effective, this strategy should be based on the size of the tax gap and the country's particular circumstances. This paper discusses some guiding principles which have provided the basis for successful reforms, including: reducing the tax system's complexity, encouraging taxpayers' voluntary compliance, differentiating the treatment of taxpayers by their revenue potential, and ensuring the reform's effective management. Also discussed are specific bottlenecks that hinder the effectiveness of the tax administration's operations.